Teachers and principals’ assessment of schools as professional learning communities in a district in the North-West Province of South Africa - D. Nkengbeza; J. Heystek (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія", 2023)
As researchers continue to seek strategies to bring systemic change in schools, many have turned to professional learning communities due to the valuable possibilities that these communities offer in reforming schools. The study aims to analyse how teachers and principals in the Dr Kenneth Kaunda District in the North-West Province of South Africa perceive their schools as professional learning communities. A quantitative approach was used to sample 87 schools for this study. Questionnaires were given to 1,260 teachers and principals in this district. The questionnaire was based on the conceptual framework of professional learning communities. The Statistical Package for the Social Sciences software program was used to analyse the data. Assessing schools as professional learning communities remains a significant way to re-examine educational institutions to determine their performance outcome. The main findings included respondents who strongly agreed to all the core components ranging from 21% (Supportive conditions – structures) to 28% (Shared supportive leadership and Supportive conditions – relationships). Respondents who agreed with all the core components rated all the components above 50% and ranged from 55% (Supportive conditions – structures) to 65% (Additional statements). While respondents who disagreed ranged from 9% to 18%, respondents who strongly agreed only ranged from 1% to 6%. Principals rated their schools as professional learning communities more than the teachers. This study also established other problems facing educational institutions in this district, adding to those already highlighted by previous researchers. Schools should be encouraged to use this self-assessment method for their respective evaluations. This article is intended mainly for teachers and principals and all those who are involved in schools' reconstruction, including the Ministry of Education